Judgment made by John Satter - Satter, John.
Judgment made by Satter against Ephraim Robins of Mansfield, Conn., for breach of Sabbath.
Justice of the peace, Windham County, Conn.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Robins, Ephraim; Sunday legislation -- Connecticut; Mansfield (Conn.) -- History; Windham County (Conn.) -- History; Justices of the peace